Criminal liability and prosecution of Islamic State fighters in Iraq - Ferlin, Anica (Varstvoslovje, 2021)
Purpose: This paper summarises the operation of the Islamic State in Iraq and includes a review of law enforcement by the authorities. The purpose of this paper is to add to the body of expertise by presenting the measures taken by the authorities to prosecute fighters of this terrorist organisation. Methods: The descriptive research methodology was applied when reviewing primary and secondary sources and to interpret the data obtained from interviews, which provide practical insights into the subject matter. Findings: The results show that the Islamic State did commit war crimes, crimes against humanity and crime of genocide in Iraq. However, at the international level and to date, no individual has been held accountable for these crimes. As Iraq is not a partner in certain international instruments, it is not possible to prosecute such acts in the country where the acts were committed. In the absence of a national strategy to prosecute suspected Islamic State fighters, processes under counter-terrorism law are thus being carried out in Iraq. The available data point to violations of the rights of suspects of fair prosecution process and the need to categorise suspects according to the severity of the crimes, which has been introduced to some extent only in Iraqi Kurdistan. In addition to prosecution, de-radicalisation must be included in the process of reintegrating Islamic State fighters into society, and thus procedures to achieve this need to be developed. At the level of society, it is necessary to address risk factors that could lead to radicalisation and to establish mechanisms to detect and prevent it. Practical Implications: The paper identifies some shortcomings related to the prosecution of the Islamic State in Iraq, and indicates the direction of further necessary practical measures that should be taken to guarantee effective and fair prosecution of Islamic State fighters, and the limitation of the risk of further radicalisation. Originality: The content of the article deals with a relatively poorly researched area and is to some extent based on interviews with government officials in Iraqi Kurdistan who have highlighted challenges that will need to be addressed in the future.
Keywords: crimes against humanity; genocid; genocide; Irak; Iraq; Islamic State; Islamska država; kazenski pregon; prosecution; vojni zločini; war crimes; zločini proti človeštvu